INTA Agency policies in the horticultural agglomerate of La Plata (Buenos Aires, Argentina) 2000-20 - García, Matías (Universidad Nacional del Litoral, 2021)
In search of advancing with the characterization of the agents and companies that explain the functioning and dynamics of the horticultural agglomerate of La Plata, it is proposed to identify and analyze the policies of the Rural Extension Agency of La Plata (AER La Plata). For this, an analysis of the organizational performance and its main policies was carried out. The AER La Plata is the protagonist of the platense horticultural agglomerate, providing new services and modifying the model. Said changes are carried out in the sense of adopting and adapting technology (conventional and alternative) within a heterogeneous social structure, basically orienting its policies for the majority and most vulnerable stratum of producers, advocating for its organization and for productive alternatives and commercial. It is concluded that the actions of INTA Agency (analyzed) are not of cooperation or competition to promote the mere growth of the territory, but rather that it functions as a counterbalance in the framework of a stage of development that exacerbates inequalities.